Collaboration of UMP UTHM Volunteers UMP Kilau to help flood victims in Batu Pahat - Mimi Rabita, Abdul Wahit (2023)
BATU PAHAT, 20 March 2023 - A total of 100 UMP Kilau volunteers consisting of students and staff of Universiti Malaysia Pahang (UMP) and Prihatin Universiti Tun Hussein Onn Malaysia (UTHM) volunteers mobilised the Johor 2023 Post-Flood Relief Mission in Batu Pahat recently.